Differences In Lipid Profiles In Diabetes Mellitus Patients Based On Cigarette Consumption - Fihiruddin, Fihiruddin; Putri, Ananda Kinanti; Manu, Thomas Tandi (Jurnal Analis Medika Biosains (JAMBS), 2025)
Diabetes mellitus (DM) is a metabolic condition characterized by hyperglycemia and abnormalities in protein, lipid and carbohydrate metabolism. Smoking is one thing that can cause DM. Smoking as a risk factor for insulin resistance. An increase in lipid profile is directly related to insulin resistance, which increases blood sugar levels by increasing lipolysis and decreasing lipogenesis in fat cells. To determine differences in lipid profiles (total cholesterol, HDL, LDL, triglycerides) in diabetes mellitus sufferers based on cigarette consumption. This research is Analytical Observational using secondary data with an approach Cross Sectional. The sampling method used in this research was purpossive sampling. Data was collected using medical record data on the lipid profile of 48 samples of diabetes mellitus sufferers who consumed cigarettes and analyzed using statistical tests Paired Sample t-test. Were that the mean levels of total cholesterol, HDL, LDL and triglycerides in diabetes mellitus patients who consumed less than 20 cigarettes per day were 228.8 mg/dL, 49 mg/dL, 127.4 mg/dL and 144.4 mg/dL. The mean levels of total cholesterol, HDL, LDL and triglycerides in diabetes mellitus sufferers who consumed more than 20 cigarettes per day were 185.3 mg/dL, 32.7 mg/dL, 116.7 mg/dL and 148 mg/dL. There is a significant difference between the HDL lipid profile in diabetes mellitus patients who consume less than 20 cigarettes per day and more than 20 cigarettes per day.